ONLINE LEARNING ASSESSMENT USING THE RECORDING ZOOM MEDIA AT TK COR JESU MARSUDIRINI - Susanti, Maria Assumpta Juniarti Harry; Watini, Sri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
This research is based on a number of phenomena in the field during the COVID-19 pandemic that hit the world, including our country, Indonesia, which also had an impact on the world of education, all activities were carried out online or online and carried out from home so that the level of service provided by teachers in early childhood was not optimal. due to lack of direct service. This research uses experimental research method. Collecting data by conducting experiments. The research sample was kindergarten children, totaling 10 respondents at Cor Jesu Marsudirini Matraman Kindergarten, located on Jl. Matraman Raya 129, East Jakarta. This study aims to (1) How is the effectiveness of children's online learning by using zoom? (2) Are there differences in the effectiveness of children's online learning by using zoom and before using recording zoom? The results showed; (1) The use of recording zoom meetings during learning is proven to be more effective and facilitates teachers in assessing learning and providing implementation of the learning process for early childhood students. (2) There is a significant difference between the effectiveness of children's online learning by using zoom and before using recording zoom with a moderate relationship